Surgery or stereotactic ablative radiation therapy: how will be treated operable patients with early stage not small cell lung cancer in the next future? - Bertolaccini, Luca (Ann Transl Med, 2015)
Lung neoplasm is the most influent cause of death for cancer. With the increasing of life expectancy in elderly patients and with the intensification of lung cancer screening by low-dose computed tomography, a further rise of the number of new non-small cell lung cancer (NSCLC) cases has been shown. Standard of care of early stage NSCLC patients is lobectomy but approximately 20% of them are not fit for surgery for comorbidities. Due to the high local control rates and the little adverse effects, stereotactic body radiation therapy (SBRT) also called stereotactic ablative radiation therapy (SABR), has rapidly replaced the conventional radiotherapy in not operable patients with stage I NSCLC. We review the evidence for use of SABR in medically inoperable patients with stage I NSCLC, and its possible extension of use to operable patients, from the perspectives of radiation oncologists and thoracic surgeons. Until the results of large randomized trials will be available, the multidisciplinary management, balancing during discussion the advantages/disadvantages of each treatment modality, could be the coming soon best approach for medically operable early-stage NSCLC. As a result, the minimally invasive thoracic surgery advantages and the SABR innovations will be translated into real clinical benefits.